An investigation of wind resources in the Adrar Region (Southern Algeria) - Benmedjahed, Miloud; Maouedj, Rachid; Mouhadjer, Samir; Dahbi, Abdeldjalil; Saba, Djamel; Touahri, Tahar (International Journal of Applied Power Engineering (IJAPE), 2021)
The aim of this article is to objectively analyze the wind atlas map of the Adrar region at 10 m from the ground, in order to classify these speeds according to the PNL (Northwest Pacific Laboratory) classification, then develop a separation velocity map in the area studied,Â  finally, We finished this work with an application on the Adrar locations, to estimate the annual, seasonal, and monthly energy produced by Whisper200 wind turbines, using the Rayleigh distribution, in order to process the wind data collected every 3 hours from 01/01/1961 to 12/31/ 2018. The northeast zone of the studied region belongs to the fourth classes of classification PNL, In other words, it is a region suitable for wind applications (by wind farm or isolated wind turbine), The surface of this area equal to 16587 kmÂ², in this area we locate two sites Kaberten and Aougroute, while the second PNL class is divided into seven zones; this wind speed class is favorable for the installation of isolated wind turbines or hybrid systems. The main cities are located in these regions such as Adrar, Timimoune, Regagne, Aoulef, Bordj Baji Mokthar and Timaiaouine.